Evaluation of Carotid Artery Atherosclerosis and Arterial Stiffness in Cardiovascular Disease Risk: An Ongoing Prospective Study From the Kailuan Cohort - Li, Wen; Wang, Yan; Chen, Shuohua; Zhao, Jianqiu; Su, Qi; Fan, Yanfeng; Wu, Shouling; Li, Jun; Hong, Jiang (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate the potential link of carotid plaque and higher arterial stiffness to the risk of cardiovascular diseases(CVD), cerebrovascular events, and all-cause mortality. Methods: This study recruited patients who underwent carotid artery ultrasonography and measurement of brachial-ankle pulse wave velocity (baPWV) from the Kailuan Study Stroke Cohort (Tangshan, China) between June 2010 and June 2011. The effects of carotid plaque, baPWV, and their combination on cardiovascular events, including myocardial infarction (MI), cerebral ischemic stroke, cerebrovascular events, and all-cause mortality, were evaluated using Kaplan-Meier analysis and Cox proportional hazards regression. Results: Finally, 4899 participants (59.7% males; 54.18±11.52 years old) were analyzed. During a mean follow-up of 5.68±0.66 years, the incidences of cardiovascular events and all-cause mortality were 4.94‰ person-years and 7.02‰ person-years, respectively; 32.8% of participants had increased in both carotid artery atherosclerosis and arterial stiffness. A high baPWV alone was associated with an increased risk of CVD events (hazard ratio [HR]: 2.68; 95% confidence interval [95%CI]: 1.20-6.00; P=0.007) and cerebral infarction (HR: 5.92; 95%CI: 1.76-19.93; P=0.004) but not with MI or all-cause death. The combination of carotid plaque and high baPWV was highly associated with an increased risk of CVD events (HR: 4.65; 95%CI: 2.06-10.45; P<0.001) and cerebral infarction (HR: 9.21; 95%CI: 2.71-31.19; P<0.001) but not with MI or all-cause death. Similar results were observed in the Kaplan-Meier analyses. Conclusion: The combination of carotid plaque and high baPWV was associated with a high risk of CVD events and ischemic stroke. The risk prediction ability of carotid plaque combined with high baPWV was higher than for each factor alone.